A new rhynchosaur from south Brazil (Santa Maria Formation) and rhynchosaur diversity patterns across the Middle-Late Triassic boundary - Schultz, Cesar Leandro; Langer, Max Cardoso; Montefeltro, Felipe Chinaglia [UNESP] (Springer, 2016)
The rhynchosaur previously referred to as the Mariante Rhynchosaur is here formally described as a new genus and species based on two specimens: a complete skull (without the lower jaw) articulated with the three first cervical vertebrae and a set of right maxilla and dentary. Both specimens were collected at the same site in Rio Grande do Sul, Brazil, from deposits of the Santa Maria Formation considered of Ladinian (Middle Triassic) age. Diagnostic characters include the contact between prefrontal and postfrontal, a pair of deep frontal grooves, and a very deep skull. A new phylogenetic analysis recovered the new taxon as a member of the Stenaulorhynchinae, a relatively diverse clade of Middle Triassic rhynchosaurs, with records in India, east Africa, and the Americas. Evidence suggests that the extinction of that clade took place in the context of a faunal turnover across the Ladinian-Carnian boundary, when it was replaced by the much more abundant Late Triassic hyperodapedontine rhynchosaurs.
Keywords: Stenaulorhynchinae; Ladinian; Dinodontosaurus AZ; Rio Grande do Sul; Phylogeny